Looking for Age Differences in Self-Driving Vehicles: Examining the Effects of Automation Reliability, Driving Risk, and Physical Impairment on Trust - Rovira, Ericka; McLaughlin, Anne Collins; Pak, Richard; High, Luke (Frontiers in Psychology, 2019)
[Purpose] Self-driving cars are an extremely high level of autonomous technology and represent a promising technology that may help older adults safely maintain independence. However, human behavior with automation is complex and not straightforward (Parasuraman & Riley, 1997; Parasuraman, 2000; Parasuraman & Wickens, 2008; Parasuraman & Manzey, 2010; Parasuraman, de Visser, Lin, & Greenwood, 2012; Rovira, McGarry, & Parasuraman, 2007). In addition, because no fully self-driving vehicles are yet available to the public, most research has been limited to subjective survey-based assessments that depend on the respondents’ limited knowledge based on second-hand reports and do not reflect the complex situational and dispositional factors known to affect trust and technology adoption. [Method] To address these issues, the current study examined the specific factors that affect younger and older adults’ trust in self-driving vehicles. [Results] The results showed that trust in self-driving vehicles depended on multiple interacting variables, such as the age of the respondent, risk during travel, impairment level of the hypothesized driver, and whether the self-driving car was reliable. [Conclusion] The primary contribution of this work is that, contrary to existing opinion surveys which suggest broad distrust in self driving cars, the ratings of trust in self-driving cars varied with situational characteristics (reliability, driver impairment, risk level). Specifically, individuals reported less trust in the self-driving car when there was a failure with the car technology; and more trust in the technology in a low risk driving situation with an unimpaired driver when the automation was unreliable.